2012
DOI: 10.1051/0004-6361/201117247
|View full text |Cite
|
Sign up to set email alerts
|

The VLT-FLAMES Tarantula Survey

Abstract: Whether massive stars ( > ∼ 30 M ) can occasionally form in relative isolation (e.g. in clusters with M < 100 M ) or if they require a large cluster of lower-mass stars around them is a key test in the differentiation of star-formation theories as well as how the initial mass function of stars is sampled. Previous attempts to find O-type stars that formed in isolation were hindered by the possibility that such stars are merely runaways from clusters, i.e., their current isolation does not reflect their birth c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 82 publications
(117 reference statements)
2
81
0
Order By: Relevance
“…As pointed out by Bressert et al (2012), the term "isolated high-mass star formation" can be unclear. Specifically, these authors suggested three possible criteria that may suggest a high-mass star is not isolated: 1) a high-mass star is forming with other high-mass stars in a molecular cloud; 2) the formation of a high-mass star may be triggered by another high-mass star; and 3) a high-mass star was gravitationally bound (within ∼3 pc) with another high-mass star sometime in the past.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out by Bressert et al (2012), the term "isolated high-mass star formation" can be unclear. Specifically, these authors suggested three possible criteria that may suggest a high-mass star is not isolated: 1) a high-mass star is forming with other high-mass stars in a molecular cloud; 2) the formation of a high-mass star may be triggered by another high-mass star; and 3) a high-mass star was gravitationally bound (within ∼3 pc) with another high-mass star sometime in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these authors suggested three possible criteria that may suggest a high-mass star is not isolated: 1) a high-mass star is forming with other high-mass stars in a molecular cloud; 2) the formation of a high-mass star may be triggered by another high-mass star; and 3) a high-mass star was gravitationally bound (within ∼3 pc) with another high-mass star sometime in the past. Bressert et al (2012) were specifically interested in criterion 3, the least restrictive of the criteria, and found 15 candidates in the 30 Doradus region that may satisfy this criterion. This study is more concerned with the most restrictive of the criteria, criterion 1, and therefore it is more akin to the investigations of field O-stars by de Wit et al (2004de Wit et al ( , 2005 and Zinnecker & Yorke (2007), who suggested that 4-10% of all Galactic O-stars are not runaways, but formed in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evans & Howarth 2008), the formation of massive stars in relative isolation (e.g. Lamb et al 2010;Bressert et al 2012;Oey et al 2013), the structure of stellar clusters (e.g. Hénault-Brunet et al 2012a,b), the properties of the interstellar medium in the Clouds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gaia will provide an opportunity to study these issues in greater detail, as well as address questions such of whether OB associations are expanding star clusters or whether they form with low densities , and whether massive stars can form in isolated or low-density environments, or if their dynamics can explain their formation elsewhere (Bressert et al, 2012). …”
Section: The Role Of Kinematics In the Formation Of Star Clustersmentioning
confidence: 99%